The Role of Socioeconomic and Cultural Factors in Shaping Healthcare Accessibility - Setiadi (Indonesian Scientific Publication, 2024)
Access to healthcare remains a critical concern globally, particularly in low- and middle-income countries where systemic barriers persist. This narrative review aims to examine the multi-layered factors influencing healthcare access, including social, economic, policy, and cultural dimensions. Literature was sourced from major scientific databases such as PubMed, Scopus, and Web of Science using key terms like